Anthropometric indicators of obesity and their link to lifestyle and cardiovascular risk in Colorado firefighters - O'Toole, Lorin, author; Nelson, Tracy, advisor; Lipsey, Tiffany, committee member; Peel, Jennifer, committee member (Colorado State University. Libraries, 2011)
Cardiovascular disease (CVD) is the leading cause of death in firefighters as it is in the general population. Despite data promoting Colorado as the leanest state in the nation and the image of firefighters as healthy and physically fit, obesity is evident in Colorado firefighters and continues to be an important CVD risk factor. PURPOSE: To determine obesity prevalence, depending on measurement and classification, and its association with lifestyle factors and cardiovascular (CV) risk in a cohort of Colorado firefighters. METHODS: Analysis was conducted on data from 466 Colorado firefighters (41 females; 425 males). Using standard classification cut-points, prevalence of obesity was determined using body mass index (BMI), waist circumference (WC), waist to hip ratio (WHR), sagittal abdominal diameter (SAD), and percent body fat (%BF) from skin fold (SF) and hydrodensitometry (H) measurements. Lifestyle factors used in the analysis included diet, physical activity, sleep, tension and depression. Lipids, C-reactive protein (CRP) levels, predicted maximal oxygen consumption and fitness measures were also included. CV risk was assessed using the Cooper Risk Profile. Correlation statistics were run for each anthropometric measure with the above variables. RESULTS: Obesity prevalence varied by measurement: BMI=9.8% females, 19.1% males; WC=19.5% females, 18.9% males; WHR=19.5% females, 8.0% males; SAD=31.6% females, 43.5% males; %BF(SF)=17.1% females (7.3% for >35%BF), 15.1% males; %BF(H)=23.7% females (13.2% for >35%BF), 28.6% males. In both sexes, all anthropometric measures were positively correlated with triglycerides and CRP and inversely associated with high-density lipoprotein cholesterol (except BMI in females), the sit and reach test and estimated maximal oxygen consumption (except BMI in females) (p≤0.05). All anthropometric measures were significantly correlated with CV risk (p≤0.05) except WHR in females. The strongest link to CV risk was %BF(SF) in females and WHR in males. CONCLUSIONS: The prevalence of obesity in Colorado firefighters varies depending on the measure used. There are significant associations between obesity and lifestyle factors that should be further explored. Percent BF(SF) and WHR may be appropriate in assessing CV risk in populations of female and male firefighters, respectively, of similar demographics.
Keywords: BMI; obesity; firefighter; cardiovascular; body fat